EFEKTIVITAS PELAYANAN KARTU IDENTITAS ANAK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Rahmawati, Rita; Yati, Siti Murni; Purnamasari, Irma; Maruapey, Muhammad Husein; Sastrawan, Berry; Syahrudin, Dede; Muchtar, Aep Saepudin; Subagdja, Oetje; Saprudin (Jurnal Governansi, 2024)
A Child Identity Card (KIA) is a card that is officially owned by children under 17 years of age and unmarried. So far, the service has been at the Service agency. cumulatively it is still low. One of the obstacles is a lack of awareness of the benefits of children's identity cards and socialization has not been optimal. The aim of the research is to find out how effective children's identity card services are, the obstacles to the effectiveness of services, and efforts to resolve obstacles to the effectiveness of children's identity card services. The method used is descriptive quantitative. With a sample of 100 people from the community and 32 employees. Data was collected through primary and secondary data techniques. Data analysis uses a Likert scale. The results show that the overall response is that the community received a score of 3.49 in the "Good" criteria and the results of employee respondents' responses were a score of 4.09 in the "Good" criteria. The assessment of these two elements is considered good, meaning that it is an indicator of increasing ability in communication skills and document detection skills so that the services provided can minimize the number of children's identity cards. This means that the implementation of children's identity card services is said to be effective, but there are still several factors that hinder the service, including that socialization has not been carried out evenly, so improvements need to be made in terms of the socialization method to make it more effective.